UK veterans’ mental health and well-being before and during the COVID-19 pandemic: a longitudinal cohort study - Howard Burdett; Margaret Jones; Lisa Hull; David Pernet; Nicola T Fear; Simon Wessely; Danai Serfioti; Marie-Louise Sharp (BMJ Open)
Objective To investigate the impact of the COVID-19 pandemic on the health and well-being of UK ex-service personnel (veterans) before and during the pandemic, and to assess associations of COVID-19 experiences and stressors with mental health, alcohol use and loneliness.Design An additional wave of data was collected from a longitudinal cohort study of the UK Armed Forces.Setting Online survey June–September 2020.Participants Cohort members were included if they had completed a questionnaire at phase 3 of the King’s Centre for Military Health Research health and well-being study (2014–2016), had left the Armed Forces after regular service, were living in the UK, had consented to follow-up and provided a valid email address. Invitation emails were sent to N=3547 with a 44% response rate (n=1562).Primary outcome measures Common mental health disorders (CMDs) (measured using the General Health Questionnaire, 12 items—cut-off ≥4), hazardous alcohol use (measured using the Alcohol Use Disorder Identification Test, 10 items—cut off ≥8) and loneliness (University of California, Los Angeles, Loneliness Scale— 3 items-cut-off ≥6).Results Veterans reported a statistically significant decrease in hazardous drinking of 48.5% to 27.6%, while CMD remained stable (non-statistically significant increase of 24.5% to 26.1%). 27.4% of veterans reported feelings of loneliness. The COVID-19 stressors of reporting difficulties with family/social relationships, boredom and difficulties with health were statistically significantly associated with CMD, hazardous drinking and loneliness, even after adjustment for previous mental health/hazardous alcohol use.Conclusions Our study suggests a COVID-19 impact on veterans’ mental health, alcohol use and loneliness, particularly for those experiencing difficulties with family relationships. Veterans experienced the pandemic in similar ways to the general population and in some cases may have responded in resilient ways. While stable levels of CMD and reduction in alcohol use are positive, there remains a group of veterans who may need mental health and alcohol treatment services.